Go Ahead, Secret Seven - Blyton, Enid (London Hodder Children's Books, 2004)
The Secret Seven are outraged. A sinister-looking man has landed George in trouble. The gang decide to spy on the stranger, they are convinced he's up to no good. But will they just make a bad situation worse?
Keywords: Childern's Literature - Fiction : Adventure